Re-analysis of pluvial precipitation in southern Brazil - Nery, Jonas Teixeira [UNESP] (2014)
This study examined precipitation in southern Brazil based on a data set provided by the Brazilian National Water Agency, covering the period from 1976 to 2010. Data were homogenized using the R software and the Climatol subroutine, which allow completing missing data. Isohyets were drawn using the Geostatistics software to obtain a semivariogram for each analysis. There was a remarkable interannual variability in this region, with positive anomalies in the warm phase (El Niño) and negative anomalies in the cold phase (La Niña) of ENSO. Also, the responses of this variability were not uniform in the entire region, since there was variability from year to year and from event to event.